Peran Financial Technology dalam Hukum Islam sebagai Upaya Preventif terhadap Tindak Pemalsuan Uang - Rif'ah, Sifwatir; Rozin, Ahmad (Program Studi Hukum Ekonomi Syariah, 2025)
The circulation of counterfeit money threatens the stability of the Indonesian economy. This study aims to analyze the role of financial technology in preventing the circulation of counterfeit money at UIN Alauddin Makassar from the perspective of sharia law, through a literature study from various sources. The method used is a qualitative approach with a literature study approach from scientific journals, books, and trusted sources related to financial technology and sharia law. The results of the study show that fintech, through innovations such as digital wallets and peer-to-peer lending, can be an effective preventive strategy in minimizing cash transactions and risks such as the circulation of counterfeit money, but its implementation must be in accordance with sharia principles, such as the prohibition of usury and transparent transactions. Thus, financial technology has great potential to prevent the circulation of counterfeit money and its development needs to be supported by increased digital literacy and collaboration between stakeholders to create a more stable and reliable financial system whose implementation is in accordance with the provisions of sharia law.